Unseen Challenges, Unheard Voices, Unspoken Desires: Experiences of Employment by Malaysians with Physical Disabilities - Suet Leng Khoo,; Ling Ta Tiun,; Lay Wah Lee, (Kajian Malaysia, 2013)
As Malaysia continues her trajectory to be a developed nation, the right towards equitable employment opportunity for Malaysians with disabilities has come to the fore. This article aims to assimilate the experiences regarding employment from Malaysian employees with physical disabilities. The novelty of this article is in making known their "unseen challenges, unheard voices and unspoken desires" regarding employment so that a pragmatic policy response can be formulated. Significantly, this article highlights that it is Malaysia's disabling environment and workplace barriers that impede Malaysians with physical disabilities from progressing in the world of work. This study involves 287 Malaysians with physical disabilities. The time has come for Malaysians with physical disabilities to earn their lawful right to equitable employment and to enjoy a better quality of life. Any further delay in achieving these aspirations reflects the lack of political will and absence of public commitment to include and integrate them into mainstream society.